Sialylation of cell surface glycoconjugates modulates cytosolic galectin-mediated responses upon organelle damage: Minireview - Weng, I-Chun; Chen, Hung-Lin; Lin, Wei-Han; Liu, Fu-Tong (Glycoconjugate journal, 2023)
Sialylation is an important terminal modification of glycoconjugates that mediate diverse functions in physiology and disease. In this review we focus on how altered cell surface sialylation status is sensed by cytosolic galectins when the integrity of intracellular vesicles or organelles is compromised to expose luminal glycans to the cytosolic milieu, and how this impacts galectin-mediated cellular responses. In addition, we discuss the roles of mammalian sialidases on the cell surface, in the organelle lumen and cytosol, and raise the possibility that intracellular glycan processing may be critical in controlling various galectin-mediated responses when cells encounter stress.